Growth of juvenile turbot in response to food pellets contaminated by fuel oil from the tanker 'Prestige' - Saborido-Rey, Fran; Domínguez-Petit, Rosario; Tomás, Javier; Morales-Nin, Beatriz; Alonso-Fernández, Alexandre (Marine Ecology Progress Series, 2007)
9 pages. Juvenile turbot Scophthalmus maximus were kept in captivity and were fed a prepared food contaminated with 5 levels of seawater-accommodated fuel oil, from 2.4 ± 0.35 to 48.2 ± 2.2 mg/g food. Oil that had been recovered from that released by the tanker 'Prestige' was used. Fish (n = 202) were individually tagged while length and weight were recorded. They were then placed randomly in 6 different tanks (1 control and 5 treatments, 32 to 35 individuals in each. For 6 wk, they were fed 3 times daily. At the end of the experiment, the fish were sacrificed, and length and weight recorded. At the beginning of the experiment, there were no significant differences in fish size and weight among tanks. After the treatment, greater oil concentration significantly reduced growth rate in size and weight. However, probably due to competition, smaller fish did not demonstrate notable growth during the experiment in any tank, while larger fish grew more in the tanks with lower oil concentrations in the food. Increasing oil concentration also reduced food consumption by individual fish. However, the reduced feeding rate alone did not explain the reduced growth rate, which was probably also the result of a major reduction in the ability for food energy conversion. Peer reviewed